Planning Optimization Technology Study Cathodic Protection As Anti Corrosion On Subsea Pipelines - Sabaruddin Rahman (Collaborate, 2023)
Subsea pipes are a tool for flowing water, oil and gas fluids. By using this underwater pipe installation, fluids can be transferred from one place to another, from a production unit to another production unit, from a storage unit to a processing unit, and from a process transferred to a storage unit. During the production process, safety must be guaranteed to avoid fatal damage such as anchor drag, sinking ships, nets or trawls and other factors such as pipe corrosion. To prevent corrosion in pipes, we need appropriate and practical solutions. We can prevent this from happening by conducting a literature study regarding the application of optimization planning for cathodic protection in pipes. The design and analysis process discusses cathodic protection analysis, which refers to the DNV GL-RP-F103 standard criteria. Additional discussion is carried out as an optimization step, namely analyzing the type of paint used based on DNVGL-RP-B401.